Systematic Improvements Aimed at Improving Exclusive Breastfeeding Rates in Los Angeles County [31I]. (May 2018) - Eskander, Ramy N.; Bender, Nicole; Buzad, Paul; Jackson, Ashaki; Saleeby, Erin
Abstract : INTRODUCTION: Disparities in exclusive breastfeeding rates vary widely between institutions, with communities of low resources often demonstrating lower rates of exclusively breastfed infants. We evaluated how, in a tertiary care academic setting, systematic changes to an electronic health record system can impact the rates of exclusively breastfed, term infants, not admitted to the Neonatal ICU. METHODS: We collected baseline data on exclusive breastfeeding rates through discharge on women who delivered within the Los Angeles County Department of Health Services system from July 2015 through June 2016 (Group 1). Beginning July 2016, a campaign was deployed aimed at educating patients & staff on the benefits of exclusive breastfeeding (Group 2). In December 2016, in addition to education, we modified our newborn feeding protocol within the Electronic Health Record System (Group 3). We then compared baseline exclusive breastfeeding rates, to the following 6 and 12 months. RESULTS: While no statistical difference existed in monthly exclusive breastfeeding rates between Group 1 and Group 2, following removal of formula from system options, a summary t -test analysis revealed a notable difference in rates between Group 2 and Group 3. Group 3 had a higher rate of exclusively breastfeeding women (M=53.90, SD=5.64) than Group 2 (M=40.57, SD=3.09); t(10)=-7.41, P<.001. Exclusive breastfeeding rates rose to 54%. CONCLUSION: Making small, systematic changes to an electronic health record can have a significant impact on provider behavior, ultimately leading to significant increases in the rate of exclusive breastfeeding through hospital discharge.